Analisis Perbandingan Kebijakan Luar Negeri Amerika Serikat terhadap Konflik Israel-Palestina pada Era Pemerintahan Barack Obama (2009-2017) dan Donald Trump (2017-2021) - Azzahra, Waode Fatimah; Nashir, Asep Kamaluddin (Jurnal ICMES, 2025)
The United States, under the administrations of Barack Obama and Donald Trump, demonstrated stark differences in their foreign policy approaches to the Israel–Palestine conflict. Obama emphasized a normative and persuasive strategy by supporting the two-state solution as a means to bring both parties to the negotiating table. In contrast, Trump adopted a more aggressive and controversial approach, exemplified by the launch of Trump's Peace Plan and the relocation of the U.S. Embassy to Jerusalem. This research aims to compare the foreign policy directions of both presidents, with a particular focus on how internal factors and idiosyncratic characteristics shaped their decision-making processes. Using a qualitative approach and the idiosyncratic theory as the analytical framework, the research examines each leader's background, leadership style, and policy preferences. The findings suggest that Obama tended to favor multilateralism and diplomacy, while Trump prioritized a more transactional approach. The research concludes that idiosyncratic factors played a significant role in shaping the United States' foreign policy approach to the Israel–Palestine conflict.